1997
DOI: 10.1021/jp971305b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analyses and Triacylglycerol Polymorphs with FT-IR Techniques. 2. β‘1-Form of 1,2-Dipalmitoyl-3-myristoyl-sn-glycerol

Abstract: On the basis of the assignments of the methylene wagging bands described in the preceding paper (Part 1), FT-IR studies have been applied to the ′ 1 -form of 1,2-dipalmitoyl-3-myristoyl-sn-glycrerol (PPM). PPM has the most stable form of ′-type, in contrast to ordinary triacylglycerols, which have the most stable form of -type. The degrees of inclination of the acyl chains with respect to the lamellar interface were determined by two FT-IR techniques of attenuated total reflection and oblique transmission. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The same property was observed in the two components of scissoring modes, reflecting the O ⊥ subcell packing (9). The complexity in the polarization properties of these two components was not clarified, in contrast to those of the typical O ⊥ subcell structure which was observed in β′ 1 of ppm (10). Figure 5 shows the FTIR spectra of the γ, β′ 2 , and β′ 1 of SRS, compared to the β form of tristearin (SSS) in the methylene-wagging progression bands region of 1500 to 1100 cm −1 as shown in Table 2 (11).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The same property was observed in the two components of scissoring modes, reflecting the O ⊥ subcell packing (9). The complexity in the polarization properties of these two components was not clarified, in contrast to those of the typical O ⊥ subcell structure which was observed in β′ 1 of ppm (10). Figure 5 shows the FTIR spectra of the γ, β′ 2 , and β′ 1 of SRS, compared to the β form of tristearin (SSS) in the methylene-wagging progression bands region of 1500 to 1100 cm −1 as shown in Table 2 (11).…”
Section: Resultsmentioning
confidence: 98%
“…From these data, it can be suggested that the stability and ordered conformation of the β′ 2 and β′ 1 forms of SRS are due to the presence of hydrogen bonds in the OH groups of ricinoleic acid moiety. The occurrence of β′ forms has been reported in the monoacid (17,18) and mixed-acid TAG (10). In several palmitoelaidic triglycerides, three polymorphic forms, α, β′ 2 , and β′ 1 , have been reported (19), where all polymorphs crystallized in the double chain-length packing.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to X-ray diffraction, a number of other techniques are employed in the identification of the different polyrnorphic forms; as mentioned before, infrared vibrational spectroscopy has been used (Amey and Chapman, 1984;Chapman, 1960a;Chapman, 1964;Freeman, 1968;O'Connor et ai., 1955;Yano, 1998;Yano et al, 1997a;Yano et al, 1997b). Nuclear magnetic resonance (NMR) measurements have also been used to study the molecular mobility in polymorphs (Arishima et al, 1996;Boceik et al, 1985; Calaghan and Jolly, 1977;Chapman, 1960b;Eads et al, 1992;Gibon et al, 1986;Hagemann and Rochfus, 1983;Norton et ai., 1985).…”
Section: Orthrhombicmentioning
confidence: 99%
“…It is also worth to comment on changes occurring in the 1150–1400 cm ‐1 region in infrared spectra. A well‐known progression of wagging and twisting vibrations of CH 2 groups in this region has been assigned to different conformations of the long chains . In particular, the intensities of the β ‐phase have a shape typical for two chains in all‐ trans configuration and the third one in a gauche configuration.…”
Section: Resultsmentioning
confidence: 90%